The Influence of Product Variations, Prices and Service Quality on Customer Satisfaction in Fahreza Sport Pemalang Convection - Fahreza, Salsa; Suharti, Suharti (Economics and Business International Conference Proceeding, 2024)
This research aims to identify how product variations, prices and product quality impact customer satisfaction at the Fahreza Sport Pemalang convection for the benefit of the company and consumers. The total population in this study was 50 people, while the sample was calculated using the Slovin formula, which resulted in a sample size of 50 respondents. The sampling technique used was purposive sampling technique. Multiple linear regression analysis was used for data analysis. This kind of research is quantitative. Primary data obtained from questionnaires was used as a data source for this research. So it can be partially concluded that all independent variables have a positive and significant effect on consumer satisfaction. The Fcount value is 11.265 with an Ftable of 2.790 and a meaning value of 0.000. A significance level below 0.05 is indicative. The regression model is significant and positive for predicting the dependent variable